1997
DOI: 10.1126/science.277.5327.781
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Coherence and Collective Optical Excitations of Conjugated Molecules

Abstract: Optical spectroscopy of conjugated molecules is described by using collective electronic coordinates, which represent the joint dynamics of electron-hole pairs. The approach relates the optical signals directly to the dynamics of charges and bond orders (electronic coherences) induced by the radiation field and uses only ground-state information, thus avoiding the explicit calculation of excited molecular states. The resulting real-space picture is reminiscent of the normal-mode analysis of molecular vibration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
354
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 350 publications
(369 citation statements)
references
References 48 publications
11
354
0
Order By: Relevance
“…6 . w x We employed the CEO technique [16][17][18] to compute and analyze the optical spectra using as r an input. The molecular transition dipole is a singleelectron operator which may be expanded in the form P s Ý m c q c , where m is the transition m n m n m n m n dipole moment matrix element.…”
Section: Electronic Coherence Signatures Of Ring Openingmentioning
confidence: 99%
“…6 . w x We employed the CEO technique [16][17][18] to compute and analyze the optical spectra using as r an input. The molecular transition dipole is a singleelectron operator which may be expanded in the form P s Ý m c q c , where m is the transition m n m n m n m n dipole moment matrix element.…”
Section: Electronic Coherence Signatures Of Ring Openingmentioning
confidence: 99%
“…The numerical CEO-INDO/S procedure for calculating electronic structure has been described in detail elsewhere 12,13 . The ZINDO code was first applied to generate the INDO/S hamiltonian using geometries obtained from crystal structures of LH2 complex of Rs.…”
Section: Methodsmentioning
confidence: 99%
“…We next calculated the Hartree-Fock ground-state density matrices which are the input to the following CEO calculation. The CEO procedure 12,13 was finally applied to compute the linear-absorption spectra and the relevant transition density matrices (denoted the electronic normal modes ξ ν ), which connect the optical response with the underlying electronic motions. Each mode is a matrix representing the electronic transition between the ground state |g> and an electronically excited state |ν>: ξ ν =<ν|c m + c n |g>, where c m + (c m ) are creation (annihilation) operators of an electron at the m'th atomic orbital.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By using 3D real-space analysis [19][20][21][22][23][24], we studied the properties of charge and energy transfer, transition of the dipole moment, electron-hole coherence and delocalization of compounds in different solvents at excited states. From the absorption spectra, emission spectra and analysis of the 3D real-space, we found that significant red shift or blue shift of both absorption maxima and fluorescence maxima of compounds 1-4 in more polar solvents, indicating a strong intramolecular charge transfer (ICT) feature and suggests that the bigger the polarity of the solvent, the greater the shift in red or blue.…”
Section: Introductionmentioning
confidence: 99%